How best to share research with study participants? A randomised crossover trial comparing a comic, lay summary, and scientific abstract. (3rd July 2022) - Kearns, Ciléin; Eathorne, Allie; Kearns, Nethmi; Anderson, Augustus; Hatter, Lee; Semprini, Alex; Beasley, Richard
Abstract: Healthcare research is traditionally published in academic papers, coded in scientific language, and locked behind paywalls – an inaccessible form for many. Sharing research results with participants and the public in an appropriate, accessible manner, is an ethical practice directed in research guidance. Evidence-based recommendations for the medium used are scant, but science communication advice advocates principles which may be fulfilled well by the medium of comics. We report a randomised crossover study conducted online, comparing participant preferences for research results shared in the medium of a comic, a traditional lay text summary, and the control approach of a scientific abstract. 1236 respondents read all three summaries and ranked their most and least preferred formats. For the most preferred summary, the comic was chosen by 716 (57.9%), lay summary by 321 (26.0%), and scientific abstract by 199 (16.1%) respondents. For the least preferred summary the scientific abstract was chosen by 614 (49.7%), lay summary by 380 (30.7%) and comic by 242 (19.6%). Review of free-text responses identified key reasons for the majority preferring the comic over the others, which included finding this easier to read and understand, more enjoyable to consume, and more satisfactory as a medium of communication.